Investigation of the Structure-Property Relationships of Photoactive Surfactants - KELLY, ELAINE (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2018)
Surfactants are functional and versatile molecules, common to a plethora of industries and applications as emulsifying, wetting, dispersing and foaming agents. The usefulness of surfactants is a result of their amphiphilicity; possessing both hydrophobic and hydrophilic components allows for both the adsorption of the surfactant at interfaces and the formation of self-assembled structures. In this thesis, two different classes of photoactive surfactants will be studied. In both cases, light is essential, either to exact a change in the physicochemical properties and self-assembly behaviour of the surfactant solution, or, as a visual signifier for the ?switching on? of photoluminescence. The first class of photoactive surfactants presented in this work is azobenzene photosurfactants (AzoPS). Cationic AzoPS have shown promise in a range of applications, from reversible DNA compaction to controlling the flow-type in microfluidic devices. However, despite their potential, only a handful of AzoPS structures have been reported to date. Fewer reports still are to be found regarding neutral AzoPS, despite their offering many advantages over their cationic counterparts. In Chapters 4-5, a family of four neutral AzoPS will be designed with the specific aim of studying how the molecular structure of the surfactants affects both their surface tension and self-assembly behaviour. Focus will be on the use of light as an actuator to bring about significant, measurable changes in the physicochemical properties and self-assembly behaviour of azobenzene photosurfactant systems. It will be shown that through the remote application of light, AzoPS can switch between ?on? and ?off? states with respect to their degree of surface tension lowering and self-assembled structure formation. Chapter 6 will study the phenomenon of aggregation-induced emission (AIE), again depending on light and the photoresponse of the surfactant as a means to study the surfactant system. The inherent tendency of surfactants to self-assemble will be used to explore the aggregation and emission properties of an AIE-active surfactant, tetraphenylethylene sodium dodecyl sulfate (TPE-SDS). TPE-SDS will be combined with sodium dodecyl sulfate (SDS) to form mixed micelles, in order to probe the geometric and spatial requirements for aggregation-induced emission to occur using a combination of small-angle scattering and photoluminescence spectroscopy techniques. The structure-property relationships identified in this work will be crucial in directing the integration of photoactive surfactants into a wide range of applications and leading future studies into the mechanism behind aggregation-induced emission.
APPROVED
Keywords: surfactants, self-assembly, nanomaterials, soft matter, photosurfactants, azobenzene